2003
DOI: 10.1152/physiolgenomics.00095.2003
|View full text |Cite
|
Sign up to set email alerts
|

Disease genes and intracellular protein networks

Abstract: By a computational approach we reconstructed genomic transcriptional profiles of 19 different adult human tissues, based on information on activity of 27,924 genes obtained from unbiased UniGene cDNA libraries. In each considered tissue, a small number of genes resulted highly expressed or “tissue specific.” Distribution of gene expression levels in a tissue appears to follow a power law, thus suggesting a correspondence between transcriptional profile and “scale-free” topology of protein networks. The express… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
10
0

Year Published

2004
2004
2013
2013

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(12 citation statements)
references
References 25 publications
2
10
0
Order By: Relevance
“…They found that many real-world networks have higher clustering coefficient as it can be obtained from the random graph model of Erdős and Rényi and presented a new model that combines the clustering property and the idea of random connectivity in a graph [5,6]. Their work brought into focus the small-world problem of sociology [7,8] and generated extensive research on various networks [9][10][11][12][13][14][15][16]. As a result, clustering was observed in all types of the investigated graphs and thus became a general characteristic of complex networks.…”
Section: Introductionmentioning
confidence: 99%
“…They found that many real-world networks have higher clustering coefficient as it can be obtained from the random graph model of Erdős and Rényi and presented a new model that combines the clustering property and the idea of random connectivity in a graph [5,6]. Their work brought into focus the small-world problem of sociology [7,8] and generated extensive research on various networks [9][10][11][12][13][14][15][16]. As a result, clustering was observed in all types of the investigated graphs and thus became a general characteristic of complex networks.…”
Section: Introductionmentioning
confidence: 99%
“…Proteins with higher interacting partners evolve slower as mutations in protein interaction sites may disrupt the network connectivity affecting the functionality of the proteins [8], [60]–[63]. Hence, considerable lower evolutionary rates of NDD genes in contrast to non-disease genes directed us to scrutinize whether protein connectivity has any influence on their evolutionary rates differences.…”
Section: Resultsmentioning
confidence: 99%
“…The expressions were analyzed and compared with reference human genes. Disease genes were more expressed than expected which suggested a possible correspondence of their products to important nodes of intra cellular protein network [9,10]. Pulmonary surfactant proteins and lipids are essential after birth for normal functioning of lungs.…”
Section: Protein Network In Diseasesmentioning
confidence: 87%